THE GOVERNMENT'S POLITICAL WILL IN DEVELOPING INCLUSIVE EDUCATION IN INDONESIA - Dewi, Maya Puspita; Wajdi, Muh Barid Nizarudin (Universitas Nasional, 2024)
Inclusive education is one of the crucial aspects in the development of a sustainable education system in Indonesia. However, the successful implementation of inclusive education is often constrained by various factors, including the level of political will of the government in adopting policies and taking concrete steps to support them. This study aims to conduct an in-depth analysis of the Indonesian government's political will in developing inclusive education. The research method used was a descriptive study with a qualitative approach. Data were collected through policy analysis, and a literature study. Data analysis was conducted using a policy analysis framework that considers aspects such as political commitment, budget allocation and program implementation. The results show that despite several efforts by the Indonesian government to promote inclusive education, the level of political will remains a major challenge. Constraints such as inadequate policy priorities, lack of adequate budget allocations and lack of inter-agency coordination are the main factors hindering the progress of inclusive education in Indonesia. Concrete measures are needed to increase the government's political will, including increased political awareness, increased budget allocations and improved inter-agency coordination to support more effective and inclusive implementation of inclusive education in the future.